Analysis of Impacts in Electric Power Grids Due to the Integration of Distributed Energy Resources - Eduardo Marlés-Sáenz; Eduardo Gómez-Luna; Josep M. Guerrero; Juan C. Vasquez (Energies)
In the present article, the impacts that arise in electrical grids due to the integration of distributed energy resources (DER) are identified and analyzed, aiming to provide a basis from which the effects of these new technologies can be considered. To conduct this research, information was collected and analyzed, which was classified according to each of the impacts evidenced in the literature, such as technical, economic, social, environmental, sectoral, and political. Considering the classification of impacts by category, the corresponding advantages and disadvantages were highlighted, and based on this, a qualitative evaluation of the information found was conducted along with respective analyses. Thus, based on the development of this article, it can be concluded that DER influences many aspects, and according to the qualitative evaluation, clarity is provided regarding the contribution of each impact within electrical grids. It was found that, out of 100% of the impacts identified, those with the highest percentage of contribution are the technical impacts.